A Life Cycle Cost Analysis of Structural Insulated Panels for Residential Buildings in a Hot and Arid Climate - Muataz Dhaif; André Stephan (Buildings, 2021)
In hot and humid climatic conditions, cooling tends to dominate building thermal energy use. Cooling loads can be reduced through the adoption of efficient building envelope materials, such as Structural Insulated Panels (SIPs). This study quantifies the life cycle cost and operational energy of a representative case-study house in Bahrain using SIPs and hollow concrete blocks (HCBs) for the envelope over a period of 50 years. Operational energy is calculated using a dynamic energy simulation tool, operational costs are calculated based on the energy demand and local tariff rates, and construction costs are estimated using market prices and quotations. The life cycle cost is quantified using the Net Present Cost technique. Results show that SIPs yield a 20.6% reduction in cooling energy use compared to HCBs. For SIP costs of 12 and 17 USD/m2, the SIP house was cheaper throughout, or had a higher capital cost than the HCB house (breaking even in year 33), respectively. We propose policy recommendations with respect to material pricing, electricity tariffs, and energy efficiency, to improve the operational energy efficiency of houses in Bahrain and similar countries along the Arabian Peninsula.